2014
DOI: 10.1063/1.4882642
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization switching of rare earth orthochromite CeCrO3

Abstract: Positive exchange bias from magnetization reversal in La1xPrxCrO3 (x 0.7-0.85) Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 22 publications
4
64
0
Order By: Relevance
“…Below the spin reorientation transition temperature (T SR ), the weak FM moment generates an internal field (H I ) at the R 3 þ site [28]. Due to the paramagnetic effect of magnetic R 3 þ , the antiparallel coupling between R 3 þ and Cr 3 þ sometimes brings about spin reorientation [10][11][12][13][14][15], negative magnetization [16][17][18][19], and EB effects [20][21][22][23]. By changing the magnitude of external magnetic field, tunable magnetic behavior can be obtained.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Below the spin reorientation transition temperature (T SR ), the weak FM moment generates an internal field (H I ) at the R 3 þ site [28]. Due to the paramagnetic effect of magnetic R 3 þ , the antiparallel coupling between R 3 þ and Cr 3 þ sometimes brings about spin reorientation [10][11][12][13][14][15], negative magnetization [16][17][18][19], and EB effects [20][21][22][23]. By changing the magnitude of external magnetic field, tunable magnetic behavior can be obtained.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, spontaneous magnetic anisotropy induced by spin reorientation causes renewed interests in rare-earth orthochromites [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The compounds RCrO 3 (R ¼La-Lu, and Y) crystallize in orthorhombic distorted perovskite structure with four formula units per unit cell [27].…”
Section: Introductionmentioning
confidence: 99%
“…Reversal of magnetization in La 0.5 Gd 0.5 CrO 3 is due to canted opposite direction magnetic moment of Gd and Cr [7]. This type of reversal of magnetization phenomena has also been observed in La 1-x Pr x CrO 3 [8], La 1-x Ce x CrO 3 [9],and CeCrO 3 [10]. Some studies have shown that magnetization reversal would be useful for uses like Volatile memories [11,12] and spin resolving devices for charged particles [13].…”
Section: Introductionmentioning
confidence: 74%
“…Emerging technologies are increasingly predicated upon the discovery of novel functional materials that exhibit striking physical properties, such as phase transition and field-induced spin reorientation (SR) transition [1][2][3][4][5][6][7][8][9][10]. Materials, such as the rare-earth orthoferrites RFeO 3 (R = rare-earth ion) with a Pbnm structure, are of fundamental interest and technological importance for potential applications, such as inertia-driven spin switching [11], ultrafast photomagnetic recording, laser-induced ultrafast SR [12], ultrafast manipulation of spins through thermally induced SR transition [13], ambient multiferroics [14], and magnetic biasing on P-E hysteresis loops [15].…”
Section: Introductionmentioning
confidence: 99%